Syntactic avoidance in the oral production of Arab EFL learners / Tariq Monther Abed Al Hameed Al Damen - Al Damen, Tariq Monther Abed Al Hameed (2013)
This study investigated syntactic avoidance employed in the oral production of Arab EFL learners, addressing two research questions: (a) how does syntactic knowledge or the lack of it affect Arab EFL learners’ choice in producing or avoiding particular syntactic structures? (b) How and why do Arab learners resort to syntactic avoidance in their oral production? Data in the form of observations, documentary material, oral interviews, and online feedback discussions were collected from 10 Arab EFL learners enrolled in the Foundation Programme at a private college in the Sultanate of Oman. The 10 participants belonged to two groups in terms of English proficiency; 4 Foundation One (pre-intermediate) and 6 Foundation Two (intermediate) learners. Findings of the study indicate that two main factors affected the participants’ oral production; limited exposure to English and lack of syntactic knowledge. It was found that participants who were not exposed to English in their everyday life situations were less confident, more hesitant, and had a higher level of avoidance behavior towards oral communication compared to participants who were exposed to English outside the classroom. Findings also show that all participants lacked syntactic knowledge despite their varying proficiency levels, social and educational backgrounds, and exposure to English language. Four major causes of the participants’ weaknesses in syntax were identified. Participants underused the troublesome syntactic structures by using avoidance strategies. The missing syntactic structures were also discovered. Two main factors affecting the participants’ choice of avoidance were determined as well. However, it was found that proficiency level did not affect the participants’ choice of avoidance. A taxonomy of avoidance emerged as a potential contribution to the field of the study.